The Role of Generation Z as Economic Actors in the Digital Age: Analysis of the Phenomenon of Youth Entrepreneurship on E-Commerce Platforms - Deva Arta Nola; Erla Deliyana; Salwaa Mumtazah; Hasrin Putri Arti; Gama Pratama (Ecobankers : Journal of Economy and Banking, 2026)
This research aims to analyze the role of Generation Z in developing the digital economy in Indonesia, with a focus on the phenomenon of successful young entrepreneurs at a young age through the utilization of technology and digital marketing strategies. One of the real examples is a 16-year-old teenager who managed to achieve a turnover of five billion rupiah in 1.5 years through a hard selling strategy of imported hair accessories products on the e-commerce platform. This phenomenon illustrates that Generation Z has high adaptability to technological developments and the courage to innovate in the digital era. The research method used is qualitative descriptive with a case study approach. The research results show that the success of the young entrepreneur is supported by the utilization of digital marketing strategies, creativity in product branding, and the ability to read market trends quickly. This finding reinforces the view that Generation Z has great potential as a driver of the national digital economy in the future Keywords: Generation Z, Digital Economy, Young Entrepreneur, Hard Selling, E-Commerce